HABITAT BANGGAI CARDINALFISH (Pterapogon kauderni) SEBELUM TSUNAMI DI TELUK PALU - Roni Hermawan; Mohamad Akbar; Deddy Wahyudi; Mubin Mubin; Mohamad Syahril; Yeldi S Adel; Renol Renol; Radhiyatul Ula (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2021)
Earthquake and tsunami struck Palu bay on September 28, 2018, and has affected the entire coast. BCF habitat on Palu bay was lost by the tsunami. BCF depends on its habitat for survival. Banggai cardinalfish is a paternal mouthbrooder with direct development, without pelagic phase and sedentary movement. If habitat extinction occurs, there is a small chance for the population to recover naturally. The BCF spread was naturally uneven, although on a relatively uniform habitat. This research aimed at determining BCF biodiversity in the Gulf of Palu and examined the distribution of BCF in Palu bay. The Determination of BCF population was done by visual census through Fish Belt Transect method and Swim Survey method, besides the conditions and habitat composition were done by using Point Intercept Transect (PIT) method. Surveys were carried out by2 times observations with 5 meters width and the transect length in a repeat was 25 meters. The results obtained the living habitat of P. kauderni on both observation locations consist of hard corals, anemones, and sea urchins. The diversity index obtained indicated that the diversity and community stability were low, while uniformity index indicated that the distribution between individual types of reasonably uniform. In contrast, the dominance index showed that the size of the adults was more dominating on the habitat on both of the observation locations. These findings would be a reference for habitat restoration of Banggai cardinalfish (BCF) post-disaster.